The Effect of Factor XIII V34L Polymorphism in Obstructive Sleep Apnea Patients (Annals of Medical Research, 2021)
Aim: In the Obstructive Sleep Apnea Syndrome (OSAS), the organism is exposed to hypoxic effects. Chronic hypoxia has thrombotic, vasoactive and inflammatory effects on cardiovascular system. This triggers the processes progressing to cardiovascular disease. While the pathological effects to which the patients are exposed are the same, marked differences are observed between patients in the progression of OSAS. Individual protective factors are thought to be effective in the development of these differences. In  some studies, it was reported that the Val34Leu polymorphism of Factor XIII, which is also known as fibrin-stabilizing factor, might have a protective effect against cardiovascular diseases. In the light of these studies, we aimed to investigate whether this polymorphism has any effects on the development of the differences in the progression of the OSAS patients.
Keywords: Obstructive Sleep Apnea, Polymorphism, Mutation